2007
DOI: 10.1007/s00595-006-3345-z
|View full text |Cite
|
Sign up to set email alerts
|

Epiploic Appendagitis: Report of Two Cases

Abstract: Epiploic appendagitis (EA) refers to primary or secondary inflammatory disease of the epiploic appendages: peritoneal pouches of subserosal fat, which run in parallel rows beside the taenia coli of the colon. It is an uncommon but self-limiting condition, which often mimics acute appendicitis or diverticulitis. An accurate diagnosis of EA can be made by performing an abdominal computed tomography scan. Establishing a correct preoperative diagnosis is important to avoid unnecessary exploratory laparoscopy or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Both conditions lead to edema, ischemic necrosis, aseptic inflammation of the affected appendage and eventually absorption by the peritoneal cavity (5)(6)(7)15). Nevertheless, Virchow was the first to suggest that detached loose intraperitoneal bodies represent detached epiploic appendages (28). In the era of laparoscopic surgery and radiographic diagnosis, calcified detached epiploic appendages can be identified as peritoneal loose bodies, also known as 'peritoneal mice' (29,30).…”
Section: Pathogenesismentioning
confidence: 99%
“…Both conditions lead to edema, ischemic necrosis, aseptic inflammation of the affected appendage and eventually absorption by the peritoneal cavity (5)(6)(7)15). Nevertheless, Virchow was the first to suggest that detached loose intraperitoneal bodies represent detached epiploic appendages (28). In the era of laparoscopic surgery and radiographic diagnosis, calcified detached epiploic appendages can be identified as peritoneal loose bodies, also known as 'peritoneal mice' (29,30).…”
Section: Pathogenesismentioning
confidence: 99%
“…2,3 The clinical presentation of right-sided diverticulitis, particularly cecal diverticulitis, often resembles that of other causes of right lower quadrant pain. 4 Consequently, in the past, more than 70% of patients with cecal diverticulitis underwent surgery based on a preoperative assumptive diagnosis of acute appendicitis. 5,6 Fortunately, ultrasonography and computed tomography (CT) are now used effi ciently for distinguishing acute appendicitis 7 and right-sided diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although bowel habits are usually not disturbed in PAE, a few reports have described complaints such as postprandial fullness, vomiting, bloating, constipation and diarrhea. [3][4][5][9][10][11][12][13][14][15] Case collections demonstrated that diarrhea occurred in 25, 10 vomiting in 27 14 and 21 16 percent of patients with PAE. These values resemble the prevalence of carbohydrate malabsorption, with up to 30% reported for European populations.…”
Section: Discussionmentioning
confidence: 99%